The Pragmatics of Literature - Paginini, Marcello (Indiana University Press, 1987)
This translation of the work of one of the founding fathers of literary structuralism and semiotics in Italy is a timely introduction to the theoretical study of literary communication. Marcello Pagnini is a leading figure in the post-structuralist endeavor to return the text to something resembling its social matrix. He explores not only the dynamics of the author/reader rapport but also the connections between the literary text and its sociocultural and historical contexts.